Hereditary spastic paraplegia: pathology, genetics and therapeutic prospects. (2nd April 2016) - Di Fabio, Roberto; Storti, Eugenia; Tessa, Alessandra; Pierelli, Francesco; Morani, Federica; Santorelli, Filippo M.
ABSTRACT: Introduction : The hereditary spastic paraplegias (HSPs), a heterogeneous group of inherited disorders whose main clinical feature is progressive lower limb spasticity, have been reclassified following the cloning of genes associated with familial cases of hypertonic paraparesis. A consequence of the genetic classification of these disorders, based on the type of mutation detected in patients, has been an expansion of the clinical spectrum of the single entities. Paradoxically, this has made the clinical diagnosis of HSPs more complex. Areas covered : Advances in knowledge of HSPs, ranging from clinical aspects to the putative pathophysiological mechanisms, are detailed. Expert opinion : Rapid technological progress in the molecular field, applied to HSPs, has allowed the identification of 84 different disease loci and the cloning of 67 corresponding genes. Updating on recent genetic findings in the HSP field is crucial in order to increase clinician awareness of the additional features of the different forms. Clinical study of patients and their relatives remains the most valuable approach for identifying new cases and tailoring genetic counseling. Future directions in HSP research should address the mechanisms underlying the reduced penetrance of some mutations, and the issue of how novel pathological information can be translated into better care and therapies, given that the latter are currently based largely on symptom relief.